2015
DOI: 10.17957/ijab/17.3.14.224
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Identification of Harmful and Beneficial Microorganisms Associated with Replanting Disease in Rhizosphere Soil of Pseudostellariae heterophylla

Abstract: Pseudostellariae heterophylla, an important medicinal plant, has been shown to suffer from serious replanting disease that causes significant declines in both yield and quality. The objective of this study was to isolate the soil-born pathogen and antagonistic microorganism for investigation of the relationship between these microorganism and consecutive monoculture problems of P. heterophylla. In this study, we isolated the bacteria with different morphology from P. heterophylla rhizosphere soil, detected the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
(37 reference statements)
0
17
0
Order By: Relevance
“…Autotoxicity is an intraspecific allelopathy process through which plants can inhibit their growth or that of their relatives by releasing toxic chemicals into the environment ( Huang et al, 2013 ), as has been observed in both natural and manipulated ecosystems, particularly agroecosystems. According to previous studies, an imbalance in the microbial community structure and the accumulation of soil-borne pathogens induced by autotoxins are the main causes of soil sickness ( Yu et al, 2000 ; Lin et al, 2015 ; Zhang et al, 2016 ). Cucumber is one of the main vegetable crops among greenhouse plants and is planted in up 40% of the greenhouse vegetable-producing area in China; however, soil sickness problems substantially restrict cucumber production ( Yu et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Autotoxicity is an intraspecific allelopathy process through which plants can inhibit their growth or that of their relatives by releasing toxic chemicals into the environment ( Huang et al, 2013 ), as has been observed in both natural and manipulated ecosystems, particularly agroecosystems. According to previous studies, an imbalance in the microbial community structure and the accumulation of soil-borne pathogens induced by autotoxins are the main causes of soil sickness ( Yu et al, 2000 ; Lin et al, 2015 ; Zhang et al, 2016 ). Cucumber is one of the main vegetable crops among greenhouse plants and is planted in up 40% of the greenhouse vegetable-producing area in China; however, soil sickness problems substantially restrict cucumber production ( Yu et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [39] found that a phenolic acid mixture could efficiently promote mycelial growth, sporulation, and toxin production of Fusarium oxysporum, one of the most important fungal pathogens, and lead to increased replanting disease incidence of R. glutinosa. In previous studies, four phenolic acids (benzoic acid, myristic acid, cinnamic acid, and 2-butenoic acid) have been identified as potential autotoxic chemicals, and exhibited partially autotoxic effects of P. heterophylla [21,22]. Furthermore, these phenolic acids released by P. heterophylla root could be utilized efficiently by three specific pathogens (Fusarium oxysporium, Talaromyces helicus, and Kosakonia sacchari) from the soil or tissue of P. heterophylla, which resulted in increased replanting disease incidence [38,42].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have demonstrated that the phenolic acids identified in the root exudates of P. heterophylla could significantly inhibit the growth of beneficial Burkholderia sp. but promote the growth of soil-borne F. oxysporum (Lin et al, 2015; Wu L. et al, 2016). However, bio-organic fertilizer, in particular, MT containing antagonistic bacteria could rebalance the beneficial and detrimental microbial residents in soil, leading to relatively more beneficial microorganisms and relatively fewer pathogenic microorganisms ( Figure 8 ; Table 3 ).…”
Section: Discussionmentioning
confidence: 99%